Geological Structure and Tectonic Reconstruction of Botutonuo and Surrounding Areas, Gorontalo - Anggun Farwati M Abdullah; Muhammad Kasim; Ronal Hutagalung (Penerbitan Universitas Trisakti, 2021)
The research aimed to reconstruct the geological structure and tectonics based on fault, shear fracture and veins data of the Botutonuo and surrounding areas. This research was conducted with DEM interpretation method to determine the lineament pattern of rock offsets and the geological structure mapping method. Geological structure analysis was carried out by using kinematic analysis method of fault, fracture and veins data using the Win Tensor program to obtain the direction and type of stress forming it. Based on the results of the analysis, extensive stress and transtensive stress trendingN-S resulted direction of Normal Fault and Slip Fault (NE-SW). Extensional stress trending (NE-SW) is the result of reorientation stress trending (N-S) in the North Sulawesi arm which is accommodated by the Gorontalo Fault regime. Normal fault and slip fault are the 2nd order faults of the 1st order faults of Gorontalo faults.